Advances in Ad Hoc Networking c - Cuenca, Pedro; Guerrero, Carlos; Puigjaner, Ramon; Serra, Bartomeu; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of refereed international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com.
Reconfiguration and Optimization Networks -- End To End QoS Mapping Between Metroethernet and WiMAX -- A Mobility Model for Personal Networks (PN) -- Replicated Random Walks for Service Advertising in Unstructured Environments -- Sensor Networks -- ACF: An Autonomic Communication Framework for Wireless Sensor Networks -- An Autonomous Energy-Aware Routing Scheme: a Supplementary Routing Approach for Path-Preserving Wireless Sensor Networks -- FlowerNet $1 (BHow to design a user friendly Sensor Network -- Distributed Policy Management Protocol for Self-Configuring Mobile Ad Hoc Networks -- Routing Algorithms and Protocols I -- Performance Evaluation of a Protocol for Fair P2P Auctions over MANETs -- A Scalable Adaptation of the OLSR Protocol for Large Clustered Mobile Ad hoc Networks -- Security and Privacy -- Securing Multihop Vehicular Message Broadcast using Trust Sensors -- Scalable Exchange of Packet Counters in OLSR -- Intrusion Detection in Mobile Ad Hoc Networks Using Classification Algorithms -- Security for Context-Aware ad-hoc Networking Applications -- MAC Protocols -- No Ack in IEEE 802.11e Single-Hop Ad-Hoc VoIP Networks -- Constraining the network topology in IEEE 802.15.4 -- Throughput and Delay Bounds for Cognitive Transmissions -- Wireless Broadcast with Network Coding: Dynamic Rate Selection -- Routing Algorithms and Protocols II -- A Reactive Wireless Mesh Network Architecture -- MEA-DSR: A Multipath Energy-aware Routing Protocol for Wireless Ad Hoc Networks -- A New Energy Efficient Multicast Routing Approach in MANETs.s
Keywords: Computer science; Computer communication systems; Data structures (Computer science).; Computers; Management information systems; Computer Science; Computer Communication Networks; Data Structures, Cryptology and Information Theory; Information Systems and Communication Service; Management of Computing and Information Systems; Electronic books